Land size and efficiency in agriculture: the case of Ethiopian smallholder farmers. A meta-analysis - Girma Asefa, Yohannes; Ayalew Muluken, Abera (Frontiers in Sustainable Food Systems, 2024)
Even if smallholder farmers have a large share in the Ethiopian economy, they operate below their potential. Land use is fundamental in determining the efficiency of farmers. However, the effect of land size on efficiency is still a controversial issue in the country. This review was designed to determine the effect of land size on farmers’ efficiency. The random-effects model showed that the farmers with smaller land sizes (≤0.5 ha) were more efficient by 21% than the farmers with larger land sizes. Moreover, the results of meta-regression analysis showed that resource endowment, labor quality, information contact, and total income were the important moderators of the presence of heterogeneity in the effect size among the studies. It was deduced that farmers are efficient with smaller land sizes since they have resources to manage their farms appropriately. Therefore, improving farmers’ production skills, providing input subsidies, and upgrading development agents’ skills are crucial to boost farmers’ efficiency in the country.